SISTEM INFORMASI ADMINISTRASI RAWAT JALAN PADA KLINIK MULIA ASIH TANGERANG - Yohannes Yahya W; TW Wisjhnuadji; Septi Triswati (Jurusan Teknik Informatika, 2014)
Role of Information Technology in the world of business and business is needed in processing the data into a very useful information as well as the Mulia Asih Clinic is located in Tangerang. Clinic is one of the organizations working in the health field. Aiming to serve and provide a public health service that strives to provide the best service to the patient. In the course of its business, the Mulia Asih Clinic is undergoing a business process that does not have the approriate system, ranging from patient registration process, the inspection process, the process of making a statement or report generation. It is less effective so as to allow the data duplicate , or loss of data. The results achieved are able to assist in the processing of data to produce more accurate information and improve the efficiency of time that will be produced at any time when needed , no longer needed the storage of documents , because documents have been stored in the database, the difficulty in making the report manually , can be facilitated and accelerated by the presence of these systems , in the design of this information , physicians can easily obtain data on the patient's medical history patient status